Exploring the Limitations and Possibilities of Researching Mathematical Dispositions of Learners with low Literacy Levels - Graven, Mellony; Heyd-Metzuyanim, Einat (Scientia in educatione, 2020)
In this paper we share the challenges we encountered while gathering data on young learner mathematical dispositions in the form of written responses to orally administered questionnaires in a context of poor literacy and proficiency in the language of learning and teaching. Drawing on data we gathered from questionnaires with 1208 Grade 3 and 4 learners across twelve schools in the Eastern Cape South Africa we explore what is visible in learner responses and raise issues of concern in relation to aspects of learner dispositions not visible through questionnaires. Differences in literacy levels and competence in the language of instruction affects learner responses in ways that make it difficult to interpret whether differences across schools are as a result of differing mathematical dispositions or rather due to differences in literacy and articulation levels. We open up for discussion both what is gained from the data gathered and explore the challenges of gathering richer data across large numbers of learners with low levels of articulation and literacy.